1999
DOI: 10.1023/a:1022137429115
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Latent Curve Analysis to Testing Developmental Theories in Intervention Research

Abstract: The effectiveness of a prevention or intervention program has traditionally been assessed using time-specific comparisons of mean levels between the treatment and the control groups. However, many times the behavior targeted by the intervention is naturally developing over time, and the goal of the treatment is to alter this natural or normative developmental trajectory. Examining time-specific mean levels can be both limiting and potentially misleading when the behavior of interest is developing systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
166
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 42 publications
1
166
0
Order By: Relevance
“…That the GBG impact was for children at highest risk of poor outcomes, males with high levels of aggressive, disruptive behavior in the fall of first grade, is in keeping with previous reported work from our trials as well as other trials of universal preventive interventions in which intervention impact was found for the students who entered the intervention period at the highest risk (Brown and Liao, 1999;Curran and Muthèn, 1999;Muthèn and Curran, 1997;Muthèn et al, 2002;Stoolmiller et al, 2000). GBG aims at reducing aggressive, disruptive behavior in the first-grade classroom through socializing first graders to the role of student.…”
Section: Discussionsupporting
confidence: 91%
“…That the GBG impact was for children at highest risk of poor outcomes, males with high levels of aggressive, disruptive behavior in the fall of first grade, is in keeping with previous reported work from our trials as well as other trials of universal preventive interventions in which intervention impact was found for the students who entered the intervention period at the highest risk (Brown and Liao, 1999;Curran and Muthèn, 1999;Muthèn and Curran, 1997;Muthèn et al, 2002;Stoolmiller et al, 2000). GBG aims at reducing aggressive, disruptive behavior in the first-grade classroom through socializing first graders to the role of student.…”
Section: Discussionsupporting
confidence: 91%
“…For the longitudinal overweight patterns, a minimum of four observations is advised to model higher-order polynomials [17]. We were able to analyze overweight patterns in 3,550 children (90% of 3,963).…”
Section: Methodsmentioning
confidence: 99%
“…When data are missing either completely at random (MCAR) or at random (MAR) and have a multivariate normal distribution, full information maximum likelihood produces parameter estimates, standard errors and test statistics that are consistent and efficient (Arbuckle 1996) 1 . Further discussions and applications for this model may be found, for example, in Bollen and Curran (2006), Browne andDu Toit (1991), Curran andMuthén (1999), Duncan et al (2006), McArdle (1986McArdle ( , 1988McArdle ( , 1989McArdle ( , 1991), McArdle and Epstein (1987), Meredith and Tisak (1990), Muthén (1991Muthén ( , 1996, Muthén and Curran (1997), Reinecke (2005), Reinecke and Seddig (in press) and Willett and Sayer (1994). In the next section we turn to the description of our data to test the development of the different elements of GFE.…”
Section: The Latent Growth Curve (Lgm) Modelmentioning
confidence: 98%